2013
DOI: 10.3201/eid1909.120898
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium chelonaeAbscesses Associated with Biomesotherapy, Australia, 2008

Abstract: An outbreak of skin abscesses occurred in Adelaide, Australia, in association with biomesotherapy, an alternative therapy practice. Mycobacterium chelonae was identified in 8 patient and 3 environmental samples. Our findings show M. chelonae infection can be associated with alternative therapies when infection-control breaches occur. Tighter regulations of alternative therapy practices are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…1). 25,35,39–66 A 43.3% majority of articles (13 of 30) were published from South America. The next 36.7% of articles (11 of 30) were published from Europe.…”
Section: Resultsmentioning
confidence: 99%
“…1). 25,35,39–66 A 43.3% majority of articles (13 of 30) were published from South America. The next 36.7% of articles (11 of 30) were published from Europe.…”
Section: Resultsmentioning
confidence: 99%
“…The most common manifestation of extrapulmonary NTM disease is skin or soft-tissue infection. These infections usually develop after traumatic injury, cosmetic procedures, or surgery, which can expose wounds to soil, water, or medical devices contaminated with environmental mycobacteria [16171819202122]. Previous report has suggested that incidence of cutaneous NTM infection has increased nearly 3-fold during the past 30 years [12].…”
Section: Skin and Soft Tissue Infectionsmentioning
confidence: 99%
“…Rapidly growing mycobacteria (RGM), including M. abscessus complex, M. chelonae , and M. fortuitum , are increasingly encountered species causing skin and soft tissue infections. Acupuncture, contaminated ultrasound gel, mesotherapy, and injection of dermal fillers have been reported as the causes of large outbreaks in the last 2 decades [16171819202122]. M. abscessus complex and M. chelonae are frequently related to long-term steroid treatment, immunosuppression, or concurrent illnesses [21].…”
Section: Skin and Soft Tissue Infectionsmentioning
confidence: 99%
“…Recent outbreaks have been associated with contaminated ultrasound gel, injection of dermal fillers, mesotherapy, and acupuncture. [47][48][49][50][51] M. abscessus complex, M. chelonae, and M. fortuitum are most commonly encountered. Each of these species has been responsible for a significant outbreak of cutaneous disease in the last two decades.…”
Section: Cutaneous Infectionmentioning
confidence: 99%